Intrauterine Hypoxia Changed the Colonization of the Gut Microbiota in Newborn Rats - Sun, Yan; Li, Lei; Song, Jiayu; Mao, Wei; Xiao, Kaihao; Jiang, Chunming (Frontiers in Pediatrics, 2021)
Background: There is accumulating evidence suggesting a connection between gut microbiota and neonatal diseases. Hypoxia may play an important role in the intestinal lesions in a neonate. Objective: This study aims to determine whether gut microbiota differs between intrauterine hypoxia rats and healthy controls, and to identify the factors that influence the changes in the gut microbiota. Methods: We constructed the intrauterine hypoxia model with rats, collected the intestinal contents of intrauterine hypoxic newborn rats and normal newborn rats within 4 hours and on the 7th day after birth. Divided them into intrauterine hypoxia first-day group (INH1), intrauterine hypoxia seventh-day group (INH7), normal first-day group (NOR1), normal seventh-day group (NOR7). The contents of the intestines were sequenced with 16SrRNA, the sequencing results were analyzed for biological information, and the differences in the diversity, richness and, individual taxa between the groups were analyzed. Results: The abundance of the gut microbiota of neonatal rats with intrauterine hypoxia was higher than the control group. Intrauterine hypoxia altered the structural composition of gut microbiota in neonatal rats.INH1 showed increased species richness, phylogenetic diversity, β-diversity, and altered relative abundance in several taxa compared to the controls. The differences in microbiota among the four groups were significantly higher than those within the group, and the differences in the abundance and diversity of INH7 and NOR7 decreased after 7 days of breastfeeding. Functional analysis based on the cluster of orthologous groups (COG) suggested that 23 functional COG categories. Conclusion: Intrauterine hypoxia changed the initial colonization of gut microbiota in neonatal rats. It could increase species richness,β-diversity of gut microbiota, and alter relative abundance in several taxa.